Analyzing Thermal Processes in Laser Welding of Multi- Component Heat-Resistant Alloy Thin-Walled Butt Joints: A Comprehensive Modeling Approach - Sokolovskyi, Mykola; Bernatskyi, Artemii; Siora, Oleksandr; Bondarieva, Valentyna; Yurchenko, Yurii; Shamsutdinova, Nataliia; Danyleiko, Oleksandr (Universitas Ahmad Dahlan, 2023)
Niobium-based alloys are vital in high-temperature environments due to their unique chemical composition, phase structure, high density, and oxidation resistance. These alloys find extensive applications in industries such as medicine, engine manufacturing, and space technology. This study delves into the complexities of modeling laser welding processes, necessitated by the multitude of dynamic parameters specific to each surface configuration. Finite element modeling was conducted using COMSOL Multiphysics to analyze the heat transfer in butt joints between Nb-15W-5Mo-1Zr alloy plates under 400 W laser radiation power. The research employed finite element modeling to analyze heat transfer in Nb-15W-5Mo-1Zr alloy plates, considering non-uniform movement at the start and end of the welding process, Gaussian heat flux distribution along the laser spot radius, and temperature-dependent reflection coefficient. The models accounted for non-uniform movement, Gaussian heat flux distribution, and temperature-dependent reflection coefficient. The study demonstrated that thin plates of Nb-15W-5Mo-1Zr alloy can be effectively welded using specific laser processing modes, leveraging their high initial cooling rate of 1.2-1.3 s. Successful welding of Nb-15W-5Mo-1Zr alloy plates requires careful consideration of laser processing parameters. While the alloy's thermodynamic properties allow for effective welding, ensuring weld quality mandates additional production processes aimed at preventing potential part failure.